Difference in the patterns of food consumption of rural households in Bangladesh: Change in food consumption in rural Bangladesh (Journal of the Bangladesh Agricultural University, 2019)
Food consumption pattern hints the proportion of various foods that households consume to meet their nutritional requirements, which is crucial to know from the policy perspective. While several studies have documented a strong link between household dietary diversity and nutritional status of household members, especially of children; the evidence that whether or not the proportions of households’ intake of nutrients from different foods differ across the income levels is almost nonexistent. The present study fills in this void in the literature by generating evidence on variations in the consumption pattern with income in the context of a low middle-income country. By using data from a national level rural households survey, this paper finds that food consumption pattern significantly differs across income classes and notably with a rise in income households tend to substitute less nutritious food with more nutritious food. However it is found that carbohydrates dominate the rural households’ diets with few proteins, vitamins, and minerals. Hence as far as food security is concerned, policymakers need to emphasize on policies that would promote households’ behavioral change in respect of food choices. Less income inequality in the economy may also be conducive to improve national food security.J. Bangladesh Agril. Univ. 17(2): 232–235, June 2019